A post-market cluster randomized controlled trial of the effect of the TENA SmartCare Change Indicator™ on urinary continence care efficiency and skin health in older nursing home residents - Muyibat Omotunde; Fredrik Agholme; Arne Böhling; Nicole Huige; Hardy Schweigel; Daniela Hayder-Beichel; Robert Reidy; Adrian Wagg (Trials, 2023)
Abstract Background Urinary continence care for residents of nursing homes who are unable to communicate their toileting needs usually involves care aides manually checking continence products (pads) to determine the level of urine saturation prior to changing. The TENA SmartCare Change Indicator is a medical device which estimates urine saturation and notifies caregivers of the optimal time for pad changes. This study will seek to examine the effect of the TENA SmartCare Change Indicator on urinary continence care efficiency and skin health, in comparison to usual care. Methods This cluster randomized controlled trial (NCT05247047) involving older nursing home residents with urinary incontinence unable to consistently indicate their toileting needs, and their care aides, will compare technology-based and usual continence care over a period of 8 weeks. Co-primary endpoints of superiority in continence care efficiency and non-inferiority in the maintenance of skin health will be assessed. Secondary outcomes will examine the resident quality of life, sleep quality, responsive behaviours, changes in pad use and leakage episodes outside the pad. Change in care aide work engagement, job satisfaction and rushed tasks will be assessed. Benefits and challenges with the use of the device for continence care will be identified from the perspectives of the care staff. Discussion Urinary continence assessment and care in nursing homes is reported as suboptimal and threatening to dignity. Data on the utility and effect of technological solutions for improving urinary continence care are few and conflicting. If shown effective, this technological solution has the potential to improve the care for older residents and improve the working lives of caregiving staff who look after this most vulnerable section of the population. Trial registration ClinicalTrials.gov NCT05247047. Registration date is Feb 18, 2022